Legal Protection for Parties to Electronic Contracts Under the Indonesian Civil Code and the Electronic Information and Transactions Law - Kurniawan Hutabarat (Legal Frontier, 2026)
The rapid growth of digital transactions has significantly increased the use of electronic contracts in various commercial activities. However, their implementation continues to raise legal issues concerning the certainty of the rights and obligations of contracting parties. This study aims to analyze the forms of legal protection available to parties involved in electronic contracts under the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata—KUHPerdata) and the Electronic Information and Transactions Law (ITE Law), as well as to identify the challenges associated with their implementation. This research employs a normative legal research approach using statutory and conceptual approaches. The analysis is based on legislation, legal literature, and relevant judicial decisions. The findings reveal that the validity of electronic contracts remains subject to the general contractual validity requirements stipulated in the Indonesian Civil Code, while the ITE Law recognizes electronic documents and electronic signatures as legally admissible evidence. Nevertheless, practical challenges persist, particularly regarding evidentiary issues, identity authentication, and the protection of parties acting in good faith. Accordingly, regulatory harmonization and the strengthening of law enforcement mechanisms are necessary to enhance legal certainty and ensure effective legal protection in electronic transactions